¿Hacia dónde tiende este proceso de globalización? - Mejia Marcatinco, Luis (2011)
The globalization is re-forming the productive systems: it debilitates the coherence of the economic national systems and in case of the underdeveloped countries, sharpens to the end the phenomena of extroversion and vulnerability. This does that the economies and national societies turn (become) more unstable and unbalanced.